Risk Aversion and Self Insurance Utilisation: Evidence from Small and Medium Scale Business Owners in Lagos State - ABASS, Olufemi Adebowale (Annals of Spiru Haret University. Economic Series, 2022)
This study is to examined the influence of risk aversion on the adoption and utilisation of self-insurance among Small Medium Enterprises (SME) owners in Lagos State. This study employed cross sectional class of survey research design. Three hundred and fifty SME owners were selected using Taro Yamane formula and the data obtained was analyzed using correlation and t-test inferential statistics. Questionnaires were administered through convenience sampling method. The result of the study revealed a significant relationship between risk aversion and self-insurance utilisation among SME owners in Lagos State. Additionally, the result of this study also revealed that there is no significant difference between preference for conventional insurance and self-insurance among Lagos State SME owners. Based on the findings of this study, it is recommended that conventional insurers should endeavour to develop products that address the actual needs of SMEs. It is also recommended that SME owners should be highly disposed to risk improvement measures as this would help to reduce the cost of market insurance and self-insurance even if both are taken up contemporaneously.